Effect of DNA methylation, modified by 5-azaC, on ecophysiological responses of a clonal plant to changing climate - Kosová, Veronika; Latzel, Vít; Hadincová, Věroslava; Münzbergová, Zuzana (Scientific reports, 2022)
Epigenetic regulation of gene expression is expected to be an important mechanism behind phenotypic plasticity. Whether epigenetic regulation affects species ecophysiological adaptations to changing climate remains largely unexplored. We compared ecophysiological traits between individuals treated with 5-azaC, assumed to lead to DNA demethylation, with control individuals of a clonal grass originating from and grown under different climates, simulating different directions and magnitudes of climate change. We linked the ecophysiological data to proxies of fitness. Main effects of plant origin and cultivating conditions predicted variation in plant traits, but 5-azaC did not. Effects of 5-azaC interacted with conditions of cultivation and plant origin. The direction of the 5-azaC effects suggests that DNA methylation does not reflect species long-term adaptations to climate of origin and species likely epigenetically adjusted to the conditions experienced during experiment set-up. Ecophysiology translated to proxies of fitness, but the intensity and direction of the relationships were context dependent and affected by 5-azaC. The study suggests that effects of DNA methylation depend on conditions of plant origin and current climate. Direction of 5-azaC effects suggests limited role of epigenetic modifications in long-term adaptation of plants. It rather facilitates fast adaptations to temporal fluctuations of the environment.
Keywords: DNA Methylation; klimatické změny; epigeneze genetická; Genes, Plant; Climate Change; rostlinné geny; Azacitidine; lidé; Humans; metylace DNA; azacytidin; Epigenesis, Genetic